Pelatihan maharah kalam santri melalui pelaksanaan kegiatan muhadharah di Pondok Pesantren Tarbiyatul Iman Malang - Mutia, Farah; Hasaniyah, Nur (Maliki Interdisciplinary Journal, 2024)
This research aims to investigate muhadharah activities at the Tabiyatul Iman Islamic Boarding School in Malang and its contribution to the development of maharah kalam santri. The research method used is a case study with a qualitative approach. Data was collected through observation, interviews with teachers and students, as well as analysis of related documents. Research findings show that muhadharah plays an important role in improving students’ language skills, especially in understanding Arabic, pronunciation and speaking skills. Muhadharah effectively creates an environment that supports intensive Arabic language practice through providing relevant materials, interactive learning techniques, and ongoing evaluation. Santri actively participate in muhadharah activities. Challenges in implementing muhadharah include differences in the ability levels of students and a lack of reference books. It is recommended to increase the frequency of muhadharah, train teachers, and provide additional resources such as audiovisual materials. This research provides insight into the importance of muhadharah in the development of maharah kalam santri and offers practical recommendations to increase its effectiveness in the future.